Epidermal mucus of Anabas testudineus as a promising source of antibacterial and anticancer agents - Ahmed Abdulkareem Najm,; Herryawan Ryadi Eziwar Dyari,; Babul Airianah Othman,; Sharifah Sakinah Syed Alwi,; Ahmad Azfaralarriff,; Muhammad Shahid,; Siti Aisyah Sanusi,; Law, Douglas; Shazrul Fazry, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Anabas testudineus is a sturdy freshwater fish that can live in a polluted environment due to the epidermal mucus (EM) that protects the fish from pathogens or germs. This study explored the functional properties of the EM as a potential antimicrobial and anticancer agent. Inactive Pseudomonas aeruginosa was introduced into fish tanks to stimulate the production of EM. This stimulus significantly increased EM production by more than 100% after 10 days of stimulation, indicating that EM production was influenced by environmental biotic stress. In vitro antibacterial activity tests showed that EM has significant antibacterial activity against Escherichia coli (12 ± 0.23 mm) and P. aeruginosa (10 ± 0.13 mm) at the tested concentration of 1000 μg/mL. Further characterisation against cells showed that EM has a cytotoxic effect against human breast cancer (MCF7) and human melanoma (A375.S2) producing an IC50 value of 4.97 ± 0.25 and 6.27 ± 0.17 mg/mL, respectively. In contrast, no cytotoxicity against normal fibroblast skin cells (HS27) was observed. In addition, apoptosis analysis showed that EM could cause DNA fragmentation of cancer cells, while no effect on normal cells was observed. These findings indicated that EM from A. testudineus could be further studied and explored as an anticancer agent.